Karakteristik Minuman Isotonik Berbahan Baku Air Kelapa (Cocos nucifera) dengan Penambahan Buah-Buahan Lokal - Satria, Nur Imam; Maherawati, Maherawati; Fadly, Dzul (Jurnal Teknologi dan Industri Pertanian Indonesia, 2024)
Isotonic drinks are substitutes for lost body fluids, minerals to replace electrolytes lost with sweat, and sugar as an energy source. Naturally, coconut has the potential as an isotonic drink because of its mineral composition and sugars that resemble body fluids. Coconut water isotonic drinks can be added with fruit flavors to add flavor. The isotonic drink made in this study uses coconut water combined with various local fruits (soursop, red guava, orange, kweni, belimbing wuluh, and pineapple). This study aimed to determine the characteristics of isotonic drinks made from coconut water with variations of local fruit types and the characteristics of the best isotonic drinks made from coconut water and local fruits. The parameters observed were sodium content, potassium content, pH, total dissolved solids, total acid, and antioxidant activity. The data obtained were analyzed using the ANOVA test (=5%) and continued with Tukey (=5%). The results showed that the characteristics of isotonic drinks made from coconut water with variations in local fruits have different characteristics according to the characteristics of each essential ingredient. Local fruit isotonic drinks have better characteristics than commercial isotonic drinks in pH value, total dissolved solids, total acid, and antioxidant activity. The isotonic drink made from coconut water with the addition of orange juice is the best isotonic drink in this study with the characteristics of sodium content 936.00 mg/kg, potassium content 398.49 mg/kg, pH value 3.75, TPT value 6.40Brix, antioxidant activity was 88.50%, and the total acid value was 0.146%.